The owl of Minerva and the ironic fate of the progressive praxis of radical historiography in post-apartheid South Africa - du Toit, André (Kronos: Southern African Histories, 2017)
This review essay reflects on issues raised by a recent edited volume. its title and stated objectives, ’History Making and Present Day Polities’ not provide a broad and inclusive survey of post-apartheid South African riographical developments. Its main topic is the unexpected demise in the apartheid context of the radical or revisionist approach that had invigorated transformed the humanities and social studies during the 1970s and 1980s. the context of the anti-apartheid struggle the radical historians had developed plausible model of praxis for progressive scholarship, yet in the new post-heid democratic South Africa radical historical scholarship itself encountered crisis of survival. This should not be confused with a general ’crisis’ of historical scholarship in South Africa, as some of the uneven contributions to this contend, as that remains an active and diversely productive field due substantial contributions by historians not based in South Africa. If the dramatic and ironic fate of radical historical scholarship in the context of the transition a post-apartheid democracy is the volume’s primary topic, then it unfortunately fails to provide serious and sustained critical reflection on the origins and sible explanations ofthat crisis. It is argued that a marked feature of the accounts of ’history making’ provided in this volume is the (former) radical historians’ of self-reflexivity and the scant interest shown in the underlying history own intellectual trajec